034. Analysis of the sensitivity to anti-TB drugs of M. Tuberculosis isolated from patients in the Pulmonary Clinic of AUTH (June 2011-September 2014) - Papadaki, Eleni (J Thorac Dis, 2015)
BACKGROUND: Tuberculosis (TB) remains a significant problem worldwide. An important factor associated with this reemergence is the development of resistance to anti-TB drugs. OBJECTIVE: The purpose of this study is to assess the sensitivity to anti-TB drugs of M. tuberculosis strains isolated from patients in the Pulmonary Clinic of AUTH, in relation to their origin. MATERIAL AND METHODS: 103 patients [62 native (60.2%) and 41 immigrants (39.8%)] with diagnosed tuberculosis, who were hospitalized or treated as outpatients in the Pulmonary Clinic of AUTH, from 06/2011 until 09/2014 were included in the study. In 74 patients (40 native and 34 immigrants) diagnosis was microbiologically confirmed and a drug sensitivity test was available. RESULTS: Resistance to isoniazid (H) was observed in four (11.8%) immigrants and four (10%) natives (P=0.895, χ(2)=0.017), to rifampicin (R) in three (8.8%) immigrants and two (5%) natives (P=0.851, χ(2)=0.035), and to ethambutol (E) in four (11.8%) immigrants and one (2.5%) native (P=0.264, χ(2)=1.249). Resistance to any of the first line antibiotics (I, R, E) was observed in seven (20.5%) immigrants and five (12.5%) natives (P=0.532, χ(2)=0.39). There was also one case of MDR TB in a native patient and two cases of XDR TB in two immigrants. None of the above differences in the frequency of resistance is statistically significant. CONCLUSIONS: Based on the above data, the frequency of resistance in significant, but resistance does not seem to be an imported problem.